An inflammation-associated lncRNA induces neuronal damage via mitochondrial dysfunction - Olazagoitia-Garmendia, Ane; Rojas-Márquez, Henar; Trobisch, Tim; Moreno-Castro, Cristina; Rodriguez Etxebarria, Ariadne; Mentxaka, Jon; Tripathi, Ajai; Yang, Bibo; Martin Ruiz, Itziar; Anguita, Juan; Meana, J. Javier; Ding, Yiliang; et al. (Molecular therapy. Nucleic Acids, 2025)
Immune disease-associated non-coding SNPs, which often locate in tissue-specific regulatory elements, are emerging as key factors in gene regulation. Among these elements, long non-coding RNAs (lncRNAs) participate in many cellular processes, and their characteristics make these molecules appealing therapeutic targets. In this study, we have studied lncRNA LOC339803 in the context of neuronal cells, which is located in autoimmunity-associated region 2p15 and recently described to have a proinflammatory role in intestinal disorders. Using human brain samples and a wide variety of in vitro techniques, we have showed a differential function of this lncRNA in neuronal cells. We have further demonstrated the role of LOC339803 in maintaining hexokinase 2 (HK2) levels and thus mitochondrial integrity, partially explaining the implication of the lncRNA in multiple sclerosis (MS) pathogenesis. Our results show the importance of cell-type-specific studies in the case of regulatory lncRNAs. We present LOC339803 as a candidate for further studies as a mitochondrial dysfunction marker or possible therapeutic target in neurodegeneration.